Development of Virtual Learning Environment Using Canvas To Facilitate Online Learning - Jusuf, Heni; Nurdin Ibrahim; Atwi Suparman (JTP - Jurnal Teknologi Pendidikan, 2021)
The results of the study for Learning during a pandemic, several studies have resulted in dissatisfaction with the existing online learning system. This dissatisfaction is because the implementation of existing online learning is not well planned and structured. Online learning only transfers face-to-face learning to virtual face-to-face. This study aims to develop virtual learning environment (VLE) to help students learn independently and study with lecturers and friends online, following predetermined learning outcomes. The research design uses Research and Development, which uses a combination of three (3) models, the Borg & Gall model, the Step of System Approach Model of Educational Research and Development, and the Rowntree model. This research conduct at the Universitas Nasional. The research subjects were students of Electrical Engineering. Data collection techniques used are questionnaires, involving Instructional Design experts, Materials experts, Language experts, Design and Media experts, one-to-one evaluation, also testing, and evaluation in large groups. The study also used pre-test and post-test questions to determine the effectiveness of VLE and the learning materials developed. The data obtained from the results is divided into two parts, namely qualitative data and quantitative data. During the test, revealed four important things from the developed VLE, namely the interaction of discussion forums, face-to-face interaction through video conferences, time management, and problem-solving that directly received feedback. The test results show that students are happy, motivated to do practice questions, and always follow the learning process on time. The results of the pre-test and post-test showed an increase of 20.40%.